Maggot debridement therapy for diabetic foot ulcer: Experience from Maggot treatment Centers - Azad, A. K.; Wan Sulaiman, Wan Mohd Azizi; Adham, SA; Yee, BL (Pharmaceutical Research Information Group, 2016)
Objective:This study aimed to evaluate the benet of Maggot Debridement Therapy (MDT) in the treatment of diabetic foot ulcer (DFU) patient. This study records result in diabetic foot wounds treated with larva Methods: debridement versus those treated by traditional debridement alone. In this arrangement of 42 patients treated with MDT. There was no critical contrast in result among the gatherings. This study can be concluded Results: Conclusion: that MDT as powerful as traditional debridement in the treatment of diabetic foot ulcers. It would be an achievable different option for diabetic foot ulcer treatment.